Artery of Percheron Stroke: A Case Report - Navickaitė, Milda; Vilionskis, Aleksandras; Dapkutė, Austėja; Ryliškienė, Kristina (Acta medica Lituanica, 2025)
Background: The Artery of Percheron (AOP) is a vascular variant supplying both sides of the thalamus, present in up to one-quarter of the general population. AOP occlusion is a rare cause of ischemic stroke, resulting in bilateral thalamic infarction. It typically manifests as altered consciousness, gaze abnormalities, and cognitive impairment. Neuroimaging of AOP stroke is challenging, as head CT is often unremarkable. However, a diagnostic ‘V’ sign can be identified on MRI. AOP stroke is treated as other types of ischemic stroke.Case description: We present a case of a 61-year-old male with a history of alcohol abuse, diagnosed with ischemic AOP stroke. He presented with sudden loss of consciousness, third nerve palsy, and vertical gaze palsy. MRI revealed bilateral paramedian thalamic infarction with midbrain involvement. Despite conservative treatment, his condition showed minimal improvement, leaving him lethargic and dysarthric. He was discharged to palliative care after two weeks.Conclusions: AOP infarction, though rare, should be considered in patients with altered consciousness. Early MRI is essential for accurate diagnosis and timely treatment, highlighting the importance of physician awareness of this condition.
Keywords: artery of Percheron; ischemic stroke; thalamic infarct; midbrain